Book Reviewing Old Beginnings: Marjorie Watts' P.E.N. The Early Years 1921-1926 (Papers in Arts and Humanities, 2021)
This review of a 1971 book is meant to invite readers to reflect on the role P.E.N. International—a worldwide association of writers, founded in London in 1921 to promote literature and intellectual co-operation among writers—might have given the increasing challenges in our contemporary society. Describing the beginnings of the organization, the book marked P.E.N.’s Golden Jubilee. Therefore, I felt it appropriate to discuss some of the issues it addressed—that is, socializing vs. political activism—as this year, P.E.N. International turned 100.
Keywords: writers’ organizations; centenary; political activism; socializing; nostalgia